Perilaku Pengelolaan Sampah Rumah Tangga di Kawasan Pesisir Pantai - Akbar, Fajar; Sarmila, Sarmila; Hairuddin, Miftah Chairani; Ganing, Abdul (Jurnal Bahana Kesehatan Masyarakat (Bahana of Journal Public Health), 2024)
Backgroud : This problem is still a problem ini every region. Trash is often found on the coast. This is due to the behavior of some people who still throw rubbish onto the coast without thinking about the impact on the coastal environment. The research was conducted tp obtain an overview of household waste management behavior in the Babana Beach coastal area. Method : the research method used is descriptive mthod. The research location was carried out in Babana Pantai Hamlet, Mamuju District, Mamuju Regency. The total number of dsmples or total sampling with a sample size of 98 families. Data collection techniques use primary data by interviews or interview with respondents. Result : the results of research on the level of knowledge of respondents regarding waste management were more respondents who had good knowledge 93,9%. Respondents attitudents towards waste management were more respondents who had good actions at 94,9%. Respondents actions regarding waste management were more respondents who had good at 82,7%. Conclusion : the description of household waste management behavior is said to be good. The suggestions in this research are for the government to prepare TPS that can be reached by the community, so that the community avoids piles of rubbish and no longer throws rubbish into the sea.